A (possível) interface entre patrimônio cultural e turismo nas políticas públicas em Minas Gerais - Álvaro Américo Moreira Sales (2012)
Cultural heritage and tourism have a direct relation, as a cultural asset can be a touristic attraction. This relation can also take place in public policies, which are defined by the government, the main territory planner and legislator. When public policies are planned with interfaces, they can have positive impacts on preservation of cultural heritage and also in tourism structuring and promotion. The study of public policy for this research included the state level Robin Hood Act, in its cultural heritage and tourism criteria, and Touristic Circuits Policy, related to tourism. This research inquired if these public policies are part of an integrated system of planning or are just isolated. The research also asked how state public policies impact at city level, in terms of advances in tourism and cultural heritage areas, considering the guidelines on decentralization from 1988s Federative Constitution of the Republic of Brazil in 1988. This study aims to: understand the structure of public policy planning at the state and municipalities of Minas Gerais; study the relationship between cultural heritage and tourism in the state and municipality public policies in the decentralization process; and study and analyze cultural heritage state policy and its coordination degree with tourism policy. Therefore, at state level, it was analyzed the results and possible interfaces between different public levels, and then, at municipality level, it was analyzed the impacts on cultural heritage preservation and tourism promotion and structuring. São João del Rei and Coronel Xavier Chaves were selected using geoprocessing tools for empirical evidence concerning repercussions of state public policies in the municipalities. Despite the apparent success of public policy at state level, the research concluded that in the municipalities analyzed there was no progress. São João del Rei and Coronel Xavier Chaves cannot act in those specific areas other than by isolated actions, therefore, they do not articulate policies in an integrated way to preserve cultural heritage and structure and promote tourism.